Checklist of hover flies (Diptera, Syrphidae) of the Republic of Georgia - Laura von der Mark (ZooKeys, 2020)
The Caucasus Region is situated between the Black Sea and the Caspian Sea and is one of the global 'biodiversity hotspots'. The Republic of Georgia lies in the central part of the Caucasus Region with two major mountainous ranges, i.e., the Greater Caucasus and the Lesser Caucasus. Although rich in species diversity, there is a gap of knowledge in the Caucasus Region, especially on the dipteran fauna (Insecta: Diptera). Among the Diptera, the family Syrphidae is a very species-rich family. Commonly called flower flies or hover flies, syrphid species are considered essential pollinators of wild flowering plants and crops, but also important as bioindicators, as biological control agents of pests and as decomposers of organic matter. This work is the first comprehensive checklist of the Syrphidae species of the Republic of Georgia. Published syrphid records for the country are here critically reviewed and updated. In addition, new records are also provided as a result of the field work conducted to set up a Georgian-German Biodiversity Center (GGBC), a multinational approach to explore the biodiversity of the Caucasus area. A total of 2,312 specimens were studied. We report 357 different species belonging to 78 genera, with 40 species recorded from Georgia for the first time. Moreover, we were able to sequence DNA barcodes for 238 specimens representing 74 species from this country.